PERILAKU KONSUMTIF DALAM PERSPEKTIF AGAMA ISLAM - Arbanur Rasyid (Yurisprudentia: Jurnal Hukum Ekonomi, 2019)
Global behavior has an impact on people's lifestyles, namely modern lifestyles embodied by consumptive, free, hedonistic, and individualistic cultures. The investors are keen to see the people's needs that are infatuated with the consumptive modern lifestyle by establishing shopping centers (malls). In fact, the mall is no longer only functioning as a place to transact but also functions acculturation, as shopping centers that appear as places to learn and as a source of new values. In the perspective of Islam, consumptive behavior is not only a matter of useless lifestyles and even tends to enter the realm of faith. In the socio-cultural system consumerism raises many social ills which are triggered by the attitude of the takabbur for the able and envious of envy for the underprivileged. These two contradictory attitudes can give birth to an imbalance in society. Islam provides a systematic offer to prevent the emergence of a culture of consumerism by involving the role of the state and providing clear guidelines on the ethics of producer and consumer behavior and equity with the methods of zakat, infaq, sadaqah, and waqf